2015
DOI: 10.3390/v7082841
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Effect of Baicalin on Enterovirus 71 In Vitro

Abstract: Baicalin is a flavonoid compound extracted from Scutellaria roots that has been reported to possess antibacterial, anti-inflammatory, and antiviral activities. However, the antiviral effect of baicalin on enterovirus 71 (EV71) is still unknown. In this study, we found that baicalin showed inhibitory activity on EV71 infection and was independent of direct virucidal or prophylactic effect and inhibitory viral absorption. The expressions of EV71/3D mRNA and polymerase were significantly blocked by baicalin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 52 publications
2
41
1
Order By: Relevance
“…Moreover, it was also demonstrated that baicalin reduced the expressions of FasL and caspase-3, hence inhibiting EV-A71 induced apoptosis in Rhabdomyosarcoma cells (RD). Additionally, it was identified to inhibit proinflammatory cytokines by the reduction in NF-κB p65 expression [73].…”
Section: Baicalinmentioning
confidence: 99%
“…Moreover, it was also demonstrated that baicalin reduced the expressions of FasL and caspase-3, hence inhibiting EV-A71 induced apoptosis in Rhabdomyosarcoma cells (RD). Additionally, it was identified to inhibit proinflammatory cytokines by the reduction in NF-κB p65 expression [73].…”
Section: Baicalinmentioning
confidence: 99%
“…For example, out of 22 different flavonoids, six phytochemicals (apigenin, baicalein, biochanin A, kaempferol, luteolin, naringenin) were active against the avian influenza H5N1 virus in human lung epithelial (A549) cells through inhibiting nucleoprotein production [67]. Baicalin (the glucuronide of baicalein) was also active against a wide range of viruses, including enterovirus [68], dengue virus [69], respiratory syncytial virus [70], Newcastle disease virus [71], human immunodeficiency virus [72], and hepatitis B virus [73], and different mechanisms were suggested for its antiviral actions. For example, baicalin inhibits the production of HBV, the templates for viral proteins and HBV-DNA synthesis [73], and decreases IL-6 and IL-8 production without affecting IP-10 levels, as shown in a study on avian influenza H5N1 virus [67].…”
Section: Antiviral Medicinal Plants and Phytochemicalsmentioning
confidence: 99%
“…7) Baicalin has various pharmacological activities, such as anti-inflammation, anti-oxidation, anti-cancer and anti-viral. [8][9][10][11] Previous study has revealed that baicalin has anti-adipogenic effect, anti-oxidation and anti-inflammatory effect in AS. 12) However, the underlying molecular mechanism of baicalin on AS is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%